Portal vein variation and thrombosis in right lobe living donor liver transplantation - Ertuğrul, Gökhan (Journal of Surgery and Medicine, 2019)
Aim: The only definitive treatment of end stage liver disease is liver transplantation. In countries where cadaveric liver transplants are limited, living donor liver transplantation is performed. However, the presence of a variation in the portal vein of the donor, or a thrombus in the portal vein of the recipient, requires specific consideration. In this study, both of these potential limitations to living donor liver transplantation were evaluated. Patients: We designed a retrospective cohort study. From April 2014 to December 2017 we retrospectively evaluated 129 patients who underwent right lobe living donor liver transplantation in Organ Transplantation Center, Medipol University Faculty of Medicine, Istanbul, Turkey. Results: Nine (7%) of the patients underwent portal venous reconstruction due to either portal vein variation or portal vein thrombosis. In six patients (67%) reconstruction was performed due to the presence of a double PV in the right lobe graft. In three (33%) patients, a thrombus in the PV necessitated a reconstruction. Early postoperative morbidity occurred in one patient (11.1%) and mortality in one patient (11.1%). Conclusions: In this study, we found portal vein reconstructions using safely frozen iliac vein grafts.